MANAJEMEN MUTU TERPADU DALAM PENDIDIKAN ISLAM - Mulyadi Hermanto Nst (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
Educational problems faced by the Indonesian nation today, among them are: 1) the low level of equality to get education, 2) the still low quality and relevance of education; 3) the weakness of management education, in addition to the realization of the benefits of science and technology in academia and independence.                         The issues that the authors want to discuss in this paper are: 1) What is Integrated Quality Management (MMT) ?; 2) What are the Principles and Advantages of Integrated Quality Management (MMT) in Islamic Education ?; 3) How is the implementation of TQM and indicators of success In Islamic education ?. Then From the problems that the authors select, the purpose of this writing is: Explain the definition of Integrated Quality Management (TQM), Explaining Principles and Benefits TQM In Islamic Education and Identify indicators - success indicators of TQM implementation in the field of Islamic education. Total Quality Management (TQM) in the field of Islamic education the ultimate goal is to improve the quality, competitiveness of output (graduates) with indicators of both intellectual competence and skills and social competence of students / high graduates. In achieving these results, the implementation of TQM within the Islamic education organization needs to be done in a truly not half-hearted manner. By utilizing all the existing quality entities within the organization our education will not go where it is today. Keywords: Integrated Quality Management Implementation